The effect of functional fatigue protocol on volleyball functional movement screening tool scores in Professional female volleyball players - Maryam Farmanbordar; Hassan Daneshmandi; Seyed Majid Tabatabaei Nezhad (Biyumikānīk-i varzishī, 2022)
Objective The purpose of the current research is to examine the effect of functional fatigue protocol on the outcomes of functional movement screening test in professional female volleyball players. Methods In this research, the population included 40 professional active female volleyball players of premier league who had at least three years of experience in playing volleyball aging from 16 to 20 years, who were chosen as convenience sampling and were included in one group. All 40 test subjects took 12 test items in form of pre-test in which all the subjects' movements were observed and scored by the researcher. Immediately after the test, the subjects performed the functional fatigue protocol defined by Sasco and Vickins. After performing the fatigue protocol, the functional screening test for volleyball was taken again. Results The obtained results from the research shows that performing the fatigue protocol has a meaningful effect on total grades obtained on functional movement screening tests for volleyball players (P≤0.05). Conclusion The findings of this study show that in order to identify changes in the movement pattern, it is necessary to examine the screening of volleyball athletes in the state of fatigue. Identifying changes in the quality of movement in volleyball athletes in a fatigued state shows that screening of the athletes should also be done when they are in a fatigue state, so that it may be possible to identify movement patterns that may lead to injury.